2009
DOI: 10.2139/ssrn.1726732
|View full text |Cite
|
Sign up to set email alerts
|

Exchange-Rate Regime and Economic Growth: A Review of the Theoretical and Empirical Literature

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The threshold above which exchange rate volatility starts to have negative effects on economic growth varies across countries and depends on the level of development, the degree of financial development, and the exchange rate regime. Petreski (2009) finds evidence that the exchange rate regime does not affect economic growth. The literature suggests that the relationship between exchange rate and GDP growth is complex and may vary depending on the country and specific circumstances.…”
Section: Money Supply (M2)mentioning
confidence: 99%
“…The threshold above which exchange rate volatility starts to have negative effects on economic growth varies across countries and depends on the level of development, the degree of financial development, and the exchange rate regime. Petreski (2009) finds evidence that the exchange rate regime does not affect economic growth. The literature suggests that the relationship between exchange rate and GDP growth is complex and may vary depending on the country and specific circumstances.…”
Section: Money Supply (M2)mentioning
confidence: 99%
“…There is a relatively large body of literature suggesting a correlation between the real exchange rate and G.D.P. growth (Levy-Yeyati & Sturzenegger, 2002;Petreski 2009). Rodrik (2008) concluded that a weak real exchange rate could compensate for institutional weaknesses and market failures which lead to underinvestment in the traded goods sector in developing countries.…”
Section: Empirical Literaturementioning
confidence: 99%
“…McKenzie (1999) and Bahmani-Oskooee and Hegerty (2007) provide surveys of the literature that studies the impact of exchange rate volatility on trade flows. Petreski (2009) presents a review of the theoretical and the empirical literature on the relationship between exchange rate regime and economic growth. Rossi (2013) reviews the literature on exchange rate forecasting with a critical perspective.…”
Section: Introductionmentioning
confidence: 99%